2019
DOI: 10.1111/trf.15263
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune heparin‐induced thrombocytopenia and venous limb gangrene after aortic dissection repair: in vitro and in vivo effects of intravenous immunoglobulin

Abstract: BACKGROUND: Heparin-induced thrombocytopenia (HIT) is a prothrombotic disorder characterized by heparindependent antibodies that activate platelets (PLTs) via PLT FcγIIa receptors. "Autoimmune" HIT (aHIT) indicates a HIT subset where thrombocytopenia progresses or persists despite stopping heparin; aHIT sera activate PLTs strongly even in the absence of heparin (heparin-independent PLTactivating properties). Affected patients are at risk of severe complications, including dual macro-and microvascular thrombosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 41 publications
1
45
0
Order By: Relevance
“…These nine patients had severe thrombocytopenia (median platelet count nadir, 14 × 10 9 /L), with 6 of 9 having HITassociated thrombosis, and another patient with GI bleeding. As reviewed elsewhere [57,61], these 9 patients showed favorable responses to IVIG, with platelet counts rising in all patients, to a median value of >100 × 10 9 /L by five days after starting IVIG. No apparent new or progressive thrombotic events were reported, and bleeding stopped in the patient who had GI bleeding.…”
Section: The Next 20 Yearsmentioning
confidence: 64%
See 3 more Smart Citations
“…These nine patients had severe thrombocytopenia (median platelet count nadir, 14 × 10 9 /L), with 6 of 9 having HITassociated thrombosis, and another patient with GI bleeding. As reviewed elsewhere [57,61], these 9 patients showed favorable responses to IVIG, with platelet counts rising in all patients, to a median value of >100 × 10 9 /L by five days after starting IVIG. No apparent new or progressive thrombotic events were reported, and bleeding stopped in the patient who had GI bleeding.…”
Section: The Next 20 Yearsmentioning
confidence: 64%
“…By performing the SRA both in the presence and absence of heparin, they showed that heparinindependent platelet-activating properties of aHIT sera are readily inhibited by addition of IVIG in vitro. Similarly, the McMaster Platelet Immunology group has also shown that it is easier to inhibit aHIT serum-induced serotonin-release by IVIG in the absence of heparin vis-à-vis its presence ( Figure 3) [59,61].…”
Section: Autoimmune Hit (Ahit): An Updated Scientific Rationalementioning
confidence: 91%
See 2 more Smart Citations
“…4 The use of IVIG for treatment of HIT was first evaluated in the late 1980s and 90s. 5 It recently has been rediscovered and proven to provide potent and long-lasting inhibition of HIT-associated platelet activation and thrombosis. 5,6 The administration of IVIG thus potentially could compensate for the potential shortcomings of a heparin/cangrelor/protamine strategy in cardiac surgery with CPB.…”
mentioning
confidence: 99%